Bullshit in Academic Writing: A Protocol Analysis of a High School Senior's Process of Interpreting Much Ado about Nothing - Smagorinsky, Peter; Daigle, Elizabeth Anne; O'Donnell-Allen, Cindy; Bynum, Susan (Research in the teaching of English, 2010)
This article reports a study of one high school senior's process of academic bullshitting as she wrote an analytic essay interpreting Shakespeare's Much Ado about Nothing. The construct of bullshit has received little scholarly attention; although it is known as a common phenomenon in academic speech and writing, it has rarely been the subject of empirical research. This study is comprised of a protocol analysis of one writer as she attempted to produce an academic essay on a topic in which her understanding of the play's content was insufficient for the task of producing the essay. The coding system identified subcodes within the major categories of content, genre, and process that enabled the researchers to infer what is involved in academic bullshitting. The analysis found that, in the absence of sufficient content knowledge, a writer familiar in discourse conventions may employ knowledge of the genre of academic writing and processes for producing generic features to create the impression that her content knowledge is adequate. The study concludes with a discussion of the phenomenon of academic bullshitting and its implications for teaching and learning academic writing.